PENGARUH PERSEPSI TENTANG SARANA PRASARANA PERKULIAHAN DAN PELAYANAN ADMINISTRASI AKADEMIK TERHADAP KEPUASAN MAHASISWA (STUDI PADA MAHASISWA JURUSAN PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG) - Ghina Hanifa; Sri Ulfa Sentosa; Armiati Armiati (Jurnal Ecogen, 2018)
This study aims to find out and analyze: (1) The effect of student's perceptions on lecture infrastructure in student's satisfaction on the students of Department of Economics Education UNP, (2) The effect of student's perceptions on academic administration services in student's satisfaction on the students of Department of Economics Education UNP, (3) the effect of students' perceptions on lecture infrastructure and academic administration services simultaneously on student satisfaction. The type of this study is quantitative descriptive. The study population was economic education students from the class of 2014-2016, the population amounted to 273 people with a sample of 163 people taken using the proportionate random sampling method with a cluster sampling technique. Data was analyzed by analysis using multiple linear regression. The results of the study show that (1) there is a positive significant effect between the perceptions of students about lecture infrastructure facilities on student satisfaction, it can be seen from sig 0,001 < 0,05, (2) there is a positive significant effect between students' perceptions of academic administration services towards student satisfaction, as seen from sig 0,028 < 0,05, (3) there is a positive significant influence between the perceptions of students about lecture infrastructure and academic administration services simultaneously on student satisfaction, seen from sig 0,000 < 0,05. Keyword: Perceptions, Lecture Infrastructure, Academic Administration Services, Student’s Satisfaction